PENGISIAN BAHAN BAKAR SELF-SERVICE DENGAN PEMBAYARAN NON TUNAI MELALUI ANIMASI 3D BLENDER - Adriansyah, Rizky Adin; Mardiana, Ardi (Universitas Majalengka, 2025)
This study focuses on the development of a 3D animation as an educational medium for the selfservice fuel filling system integrated with cashless payment methods at gas stations. The research was motivated by the limited adoption of self-service systems in Indonesia and the increasing need for safe, convenient, and contactless transactions, especially after the COVID-19 pandemic. The study employed the Multimedia Development Life Cycle (MDLC) method consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. The testing phase was carried out in two stages: Black box Testing to evaluate functionality and usability testing with 40 respondents using a questionnaire. The results showed that the developed animation achieved user satisfaction levels of 76.75% for ease of understanding, 75.00% for cashless payment integration, and 82.50% for effectiveness as an educational tool, with an overall average of 77.84%. These findings indicate that the 3D animation is feasible and effective as a learning medium to improve user understanding of self-service fuel filling with cashless payment at gas stations.